The Effect of Profitability, Executive Character, and Company Size on Tax Avoidance: A Case Study of Manufacturing Companies on The IDX - Aditya Ramadhani Kurniawan; Sugiharto Sugiharto; Hedi Pandowo (Journal of Social Science and Humanities, 2025)
This study aims to analyze the effect of profitability, executive character, and company size on tax avoidance with leverage as an intervening variable. The population of this study consisted of 220 companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024, with a sample of 61 companies selected through a purposive sampling method. The data used are secondary data that are quantitative in nature. The analysis method used is path analysis to identify direct and indirect effects using SPSS 22 software. The data was processed using path analysis and the results showed that executive character, company size and profitability did not affect the company's tax avoidance with leverage as an intervening variable. The existence of tax avoidance practices that are still carried out by companies, it is hoped that the results of this study can be used by companies to avoid tax avoidance practices, for investors to assess tax avoidance before making decisions, and also for policy makers to detect tax avoidance